Positive Aspects In Parents with Neurodevelopmental Disorder Children - Kamila, Aldirra Naufa; Novita, Shally; Purba, Fredrick Dermawan (UNIVERSITAS PAKUAN, 2023)
Neurodevelopmental Disorder (NDD) is a neurodevelopmental disorder related to the functioning of the nervous system and brain. Parents of children with NDD experience increased stress in managing various daily chores and activities such as feeding, autonomy, leisure, and schooling of the child. However, some parents cope very well and derive great benefits from their parenting role. Several studies have found a variety of benefits for parents while caring for their children. Caregivers who reported positive aspects had better health, fewer depressive symptoms, higher parenting competence and greater family adjustment. This study is a qualitative study with a phenomenological approach that aims to find out the positive aspects that parents feel while caring for children with a diagnosis of neurodevelopmental disorder. Parents with children diagnosed with NDD (N=3) underwent a semi-structured interview process after agreeing to informed consent. The results of the study showed that the positive aspects experienced by parents during parenting were feeling the child as a source of happiness, receiving support from the community, and increased spirituality